Satisfaction and associated factors among psychiatry service users at Amanuel mental specialized hospital. Addis Ababa, Ethiopia - Kibrom, Esayas; Naser, Zebiba; Seyoum, Merga; Mengesha, Atakilit; Adem, Kemeria; Dechasa, Deribe Bekele; Asfaw, Henock (Frontiers in Psychiatry, 2022)
Background: Patient service satisfaction is the central point for the health system. Worldwide, around 450 million people suffer from mental and behavioral disorders. Clients who are dissatisfied with the service will miss appointments, abandon the treatment plan, and eventually relapse from the illness. Despite improved access to health services, the satisfaction from health institution services was decreasing from time to time and there is little information on health service consumer satisfaction. Objective: To assess the satisfaction and associated factors among psychiatric service consumers at Amanuel Mental Specialized Hospital, Addis Ababa, Ethiopia, 2021/2022. Methods and Materials: An institutional-based cross-sectional study was conducted among 420 psychiatric service users from December 15 to January 16, 2021/2022. Systematic random sampling was used. A face-face interview technique and chart review were used to collect the data and a standard and validated tool called the mental health service satisfaction scale (MHSSS) was used to measure satisfaction. The collected data was entered into EPI info version 7 and exported to SPSS version 22 for analysis. The binary logistic regression model was used to analyze the data and bivariable and multivariable logistic regression analyses were conducted to identify associated factors with satisfaction. The level of significance was reported at P-value less than 0.05. Results: The study showed that the magnitude of patient satisfaction was 63.3% (95% CI 58.3 % to 67.9%). Sex (AOR = 1.7, 95% CI (1.072-2.88)), educational status (AOR 4.2, 95% CI 1.64 to 1.8), residency (AOR = 1.8, 95% CI (1.098-3.19)), distance from the hospital (AOR 0.56, (0.34-0.93) were significantly associated with patient satisfaction at p-value less than 0.05. Conclusion: The magnitude of patient satisfaction was high. The study showed that Sex, educational status, residence, and distance from the hospital were significantly associated with satisfaction. Prioritizing care for female patients and those coming from a distance is necessary. More ever, it is preferable to routinely and continually monitor healthcare facilities so that timely feedback can be given and problems that affect patient satisfaction can be resolved.